Unraveling the Beneficial Role of Resveratrol in Fructose-Induced Non-Alcoholic Steatohepatitis with a Focus on the AMPK/Nrf2 Signaling Axis - Soha S. Zakaria; Safaa M. Hanafy (Medicina)
Background and Objectives: High fructose intake is associated with non-alcoholic fatty liver disease (NAFLD), a chronic liver disease that is on the rise worldwide. New alternatives for treatment, such as bioactive phytochemicals, are needed. The aim of this study was to investigate the beneficial role of resveratrol in treating non-alcoholic steatohepatitis (NASH). Materials and Methods: Sixty male albino rats were allocated to three groups: group I, the normal control group; group II, the fructose-enriched diet group (FED), which was fed a 70% fructose diet for six weeks to induce NASH; and group III, the resveratrol–FED group (RES + FED), which was given the same FED diet plus an oral dose of 70 mg/kg resveratrol (RES) every day for an additional six weeks. We performed histological evaluations and assessed blood lipids and liver enzymes to study resveratrol’s impact on NASH. Quantitative real-time PCR was used to assess the mRNA expression of nuclear factor E2-related factor 2 (Nrf2) in the liver samples. ELISA was used to measure Beclin 1, AMPK, IL-6, and the DNA-binding activity of Nrf2. Oxidative stress indicators, including GSH, SOD, and MDA, were evaluated spectrophotometrically. Results: Resveratrol effectively alleviated the biochemical and histopathological abnormalities associated with NASH, improving autophagy by raising Beclin 1 levels while reducing inflammation by decreasing IL-6 levels. Furthermore, resveratrol restored the liver architecture and the oxidative balance, as evidenced by the decreased MDA levels and improved antioxidant status via elevated GSH and SOD activities, as well as the activation of the AMPK/Nrf2 signaling axis. Conclusions: This study specifically examines resveratrol’s therapeutic effects in a high-fructose diet-induced NASH model, focusing on the AMPK/Nrf2 signaling pathway to address oxidative stress and autophagy, providing novel insights into its molecular mechanism of action. Resveratrol reduces NASH by boosting autophagy and activating the AMPK/Nrf2 pathway. These findings underscore the potential of resveratrol as a promising therapeutic agent that can support treatment alongside conventional medications in the management of non-alcoholic steatohepatitis (NASH).